The effects of mental symptoms of refugee adolescents on their substance use proclivity: an example of South-Eastern Turkey. - Düken, Mehmet Emin; Kaplan, Veysel (Journal of Substance Use, 2024)
Purpose: This study was conducted to examine the effects of psychological symptoms of refugee adolescents on their substance use proclivity. Methods: The study was conducted as descriptive cross-sectional research. The study was conducted with refugee adolescents living in the southeast Anatolian region of Turkey. The Brief Symptom Inventory (BSI) and Substance Use Proclivity Scale were used to determine adolescents' mental symptoms and substance use tendencies. Linear regression model and structural equation modeling were preferred in the analysis of the research. Results: It was determined that adolescents' experienced psychological symptoms that were directly related to factors such as loss of relatives and length of stay in Turkey. In the model created for adolescents' substance use tendencies, it was determined that psychological symptoms such as anxiety, depression, negative self-image and hostility were effective at a rate of 49.4%. Conclusions: It was found that refugee adolescents experienced intense mental symptoms despite the fact that many years have passed after war and migration. It was determined that the losses they experienced and smoking had most effect on these mental symptoms. It was found that the psychological symptoms of adolescents had a significant effect on their tendency to use substances.